Documentation science in Algerian law Documenting a contract for the sale of a model Property - mecheri, ramzi (Journal of Social Sciences and Humanities, 2025)
which named by documentation science ( science of Tawthik) . The Maalikis had a big proportion in this science, until they almost belonged to them. Their scholars dealt with this science by classification and authoring in a single work books, or within a judiciary book. Many scholars were known by it, and they were belonged to it thanks to large of its advantages, and the great of its importance. By this latter people protect their properties from robbery, and their honors to be violated. Until now this science is still used by Muslims and even by non Muslims that’s why we have shed light in this study on making comparison between scholars and Algerian legislator documentation, concerning the notary condition and the document. Besides to that, we make a practical example for buying a realty documentation contract in the Algerian law, trying to show how far is the Algerian legislator firm to the documentation rules which the scholars set up in their books.